Surgical Treatment of Carotid In-Stent-Restenosis: Novel Strategy and Current Management - Jost, Dominik; Unmuth, Susanne Johanna; Meissner, Helfried; Henn-Beilharz, Albrecht; Henkes, Hans; Hupp, Thomas (The Thoracic and Cardiovascular Surgeon, 2012)
Background Associated with increasing use of carotid artery stenting (CAS), the occurrence of late complications is likely to rise. The surgical strategies of CAS complications like in-stent-restenosis (ISR) are not yet to be determined. Thus different situations require individual operative techniques.This study contains our experience in the operative management for significant recurrent carotid stenosis following angioplasty and stent placement. As a novel strategy, we report successful stent removal and endarterectomy with eversion technique (ECEA).Methods Four complete stent removals were performed in three patients with three different techniques and anesthesiological protocols (general anesthesia n = 1, regional anesthesia n = 3). First stent removal with excision of common carotid artery (CCA) and internal carotid artery (ICA) following interposition of CCA-ICA with Dacron graft (n = 1). Second carotid endarterectomy with stent removal followed by patch angioplasty (n = 2). Third stent removal and ECEA and thus biological reconstruction without synthetic material (n = 1). Mean operative time was 131 minutes (±19.25). Mean follow-up was 11.5 months (±7.7). As postoperative complications, one major bleeding, one transient neurologic deficit and one postoperative neck hematoma, requiring operative revision, occurred. During a 30-day follow-up, all patients made an uneventful recovery. There was no evidence of restenosis or neurological deficit during the following postoperative controls. A review and comparison of the current surgical management and strategies in the treatment of ISR was also performed (Pubmed).Conclusion Surgical treatment of ISR after CAS is beneficial but in literature infrequently reported. We could demonstrate in this study that even stent removal and ECEA is feasible and safe with durable outcome. The current strategies are therefore extended as well as the reported performance under regional anesthesia. However, surgical treatment in ISR remains a challenging option and larger series are highly recommended.
Keywords: carotid arteries; endovascular procedures/stents; except PCI; restenosis; reoperation; stents; surgery; complications